A 24‐week double‐blind placebo‐controlled study of the efficacy and safety of the AMPA modulator S47445 in patients with mild to moderate Alzheimer's disease and depressive symptoms. Issue 1 (24th June 2019) - Bernard, Katy; Gouttefangeas, Sylvie; Bretin, Sylvie; Galtier, Stéphanie; Robert, Philippe; Holthoff‐Detto, Vjera; Cummings, Jeffrey; Pueyo, Maria
Abstract: Introduction: S47445 is a novel positive allosteric modulator of alpha‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole‐propionic acid receptors that may emerge as a favorable candidate for the symptomatic treatment of cognitive and depressive disorders in patients suffering from Alzheimer's disease (AD) of mild to moderate severity and with depressive symptoms. Methods: For this double‐blind, placebo‐controlled 24‐week phase II trial, 520 outpatients aged between 55 and 85 years, with probable AD at mild to moderate stages (a Mini‐Mental State Examination score of 24‐15 inclusive) and exhibiting depressive symptoms (Cornell Scale for Depression in Dementia [CSDD] ≥ 8) were recruited in twelve countries and randomized to 3 doses of S47445 (5‐15‐50 mg) or placebo. The primary end point was the change from baseline in the 11‐item Alzheimer's Disease Assessment Scale‐Cognitive subscale (ADAS‐Cog) total score at week 24. Secondary measures included the Disability Assessment for Dementia, Mini‐Mental State Examination, ADAS‐Cog 13‐item, CSDD, Clinical Global Impression of Change (Alzheimer's Disease Cooperative Study‐CGIC), Neuropsychiatric Inventory (NPI), and safety criteria. Results: Baseline characteristics were comparable between the 4 groups. After 24 weeks, no statistically significant treatment difference was demonstrated between S47445 (5, 15 or 50 mg/d) and placebo on cognition (ADAS‐Cog), function (Disability Assessment for Dementia), or depressive symptoms (CSDD). An improvement on neuropsychiatric symptoms assessed by NPI was evidenced at the lower dose 5 mg/d (Δ ‐2.55, P  = .023, post hoc analysis) compared to placebo. CSDD and total NPI scores improved in all groups including placebo. There were no specific and/or unexpected safety signals observed with any of the S47445 doses. Discussion: S47445 administered for 24 weeks was safe and well tolerated by patients with mild to moderate AD; the compound did not show significant benefits over placebo on cognition, function, or depressive symptoms.